Fractal Analysis of Cloud Shapes - Madhushani, K.N.R.A.K.; Sonnadara, D.U.J. (My University, 2012)
A study was carried out to investigate the fractal properties of cloud shapes. Water vapor images of clouds over the Indian Ocean region captured by the geostationary meteorological satellite METEOSAT-7 during the period of 2008 August to 2009 July were used in the present study. The fractal dimensions of cloud shapes have been calculated using the area-perimeter relationship and the box-counting method. To improve the extraction of cloud shapes, image preprocessing steps such as background subtraction and noise filtering were applied. Cloud shapes at different colour values were extracted from satellite images using the k-means clustering algorithm. The value of the fractal dimension varies between 0.8 and 1.6. The results of this work agree well with related studies carried out for both small and large clouds in the past. The average fractal dimension of clouds 7 km above ground level is 1.5±0.1.
Keywords: Fractals; Mathematical modeling